Hubungan Self-Efficacy dengan Kesiapsiagaan Bencana Gempa Bumi pada Masyarakat Parangtritis - Rafly Al Ayyubi; Widaryati Widaryati; Dwi Peihatiningsih (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Earthquakes are natural disasters that frequently occur in coastal areas, posing significant threats to the survival and well-being of local communities. Due to the high vulnerability of these regions, it is crucial for the population to possess adequate preparedness and a strong sense of self-efficacy in responding to such disasters. Self-efficacy, referring to an individual's belief in their ability to overcome challenges or manage difficult situations, is considered a key factor in preparing for and responding to earthquakes. Previous studies have shown that individuals with higher levels of self-efficacy are more likely to be better prepared for natural disasters, including earthquakes. This study aims to examine the relationship between self-efficacy and earthquake preparedness in the Parangtritis community, specifically in Dusun Sono. The primary objective of this research is to analyze the extent to which self-efficacy is related to earthquake preparedness. This study employs a descriptive correlational approach with a cross-sectional design, allowing the researcher to identify the relationship between two variables at a single point in time. A sample of 85 respondents was selected using purposive sampling, based on specific characteristics relevant to the research objectives. The respondents were from the Dusun Sono community, Parangtritis. Data were analyzed using Kendall’s Tau test to examine the relationship between self-efficacy and preparedness for earthquake disasters. The analysis revealed that 74.1% of respondents exhibited high self-efficacy, and 49.9% demonstrated good preparedness. Statistical analysis indicated a significant relationship between self-efficacy and earthquake preparedness, with a p-value of 0.000 (p<0.05), suggesting that the results are highly unlikely to have occurred by chance. Additionally, the correlation coefficient of 0.615 indicates a moderate strength of the relationship between the two variables. These findings provide strong evidence that higher levels of self-efficacy are associated with better preparedness for earthquake disasters.